Effects of pH on the growth rate, motility and photosynthesis in Euglena gracilis - Danilov, R A; Ekelund, N G (Folia microbiologica, 2001)
The influence of pH 3-10 on the growth, motility and photosynthesis in Euglena gracilis was demonstrated during a 7-d cultivation. The cells did not survive at pH < 4 and > 8, highest growth rate being detected at pH 7. Motility followed a similar pattern as growth rate. Photosynthetic response curves were shown to be of the same type over the whole pH range. High respiration was characteristic for cells grown at pH 5 and 6, the lowest one at 7. At high and also at low pH more active respiration was found which can be considered as a protective response on proton stress. Respiration was not completely inhibited with potassium cyanide. Photosynthesis was the most effective at pH 6; lower and higher pH decreased photosynthetic efficiency. pH affected more the growth rate than the photosynthesis.
Keywords: Animals; Movement; fotosyntéza; Oxygen Consumption; Potassium Cyanide; Photosynthesis; zvířata; kyanid draselný; pohyb; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; spotřeba kyslíku; Euglena gracilis